Natural products regulate mitochondrial function in cognitive dysfunction-A scoping review - Jinmei Tuo; Jinmei Tuo; Jinmei Tuo; Yan Peng; Yushuang Linghu; Ming Tao; Shiming Huang; Zucai Xu; Zucai Xu (Frontiers Media S.A., 2023)
Medicines from natural products can not only treat neurodegenerative diseases but also improve the cognitive dysfunction caused by treatments with western medicines. This study reviews the literature related to the regulation of mitochondrial participation in cognitive function by natural products. In this study, we focused on English articles in PubMed, Web of Science, and Google Scholar, from 15 October 2017, to 15 October 2022. Fourteen studies that followed the inclusion criteria were integrated, analyzed, and summarized. Several studies have shown that natural products can improve or reduce cognitive dysfunction by ameliorating mitochondrial dysfunction. These results suggest that natural products may serve as new therapeutic targets for neurodegenerative diseases.